Forbes best business mistakes : how today's top business leaders turned missteps into success - Sellers, Bob (Wiley, 2010)
Based on the experiences of some of today's most successful men and women, this book contains practical lessons that can help you learn from their personal and professional missteps. The author sat down for exclusive and revealing interviews with each